Serum carnosinase 1 is not associated with insulin resistance or glucose metabolism in a type 1 diabetes cohort - Qiu, Jiedong; Yard, Benito A.; Krämer, Bernhard; van Goor, Harry; van Dijk, Peter R.; Kannt, Aimo (Biomedicines, 2025)
Background/Objectives: Preclinical studies suggest that the deleterious effect of a high serum carnosinase 1 (CN1) concentration is attributed to its adverse effects on insulin sensitivity and glucose metabolism. However, there is little evidence for a modulating role of CN1 in glucose metabolism in humans. Methods: We measured serum CN1 concentration in an observational type 1 diabetes cohort of 172 patients in whom glucose variability (MAGE, MODD, SD of individual blood glucose, mean, and CV) was recorded by blinded continuous glucose monitoring for 5-7 days. Furthermore, insulin dose per kg body weight was compared. Results: Insulin sensitivity (insulin dosage) and glucose variability parameters did not differ between different CN1 tertiles (p > 0.05). Conclusions: There was no association of serum CN1 with indices of glucose variability in this type 1 diabetes cohort.